A CASE STUDY ON COLLEGE LEARNERS’ READING INTERESTS THROUGH WHATSAPP GROUP AMIDST VIRAL COVID-19 EMERGENCY - Fujiono Fujiono (The Ellite of Unira, 2022)
Amidst viral Covid-19 emergency, the minister of education and culture has instructed the teachers or lecturers and learners to utilize the social media as online teaching-learning process. In this case, the researchers tried to find out the college learners’ reading interests through social media (WhatsApp group). This research applied a case study design in which the data sources were interview and self-report questionnaire. The result of interview showed the college learners were interests and fun, enjoy, confident. Additionally, the college learners also had much time to read, and got new experiences. The result of self-report questionnaire described almost all college learners felt happy, enthusiastic, enjoy, confident, satisfied, belonged to WhatsApp group, better communication, and also the college learners had much time to read, a great deal of information, and academic achievement. WhatsApp group has become online teaching-learning media that can raise the college learners’ reading interests amidst viral Covid-19 emergency. The educators and learners were suggested to use the social media such as WhatsApp group as online teaching-learning media during pandemic.